A fuzzy logic evaluation of synergies and trade-offs between agricultural production and climate change mitigation - Roberta Calone; Angela Fiore; Guido Pellis; Maria Luz Cayuela; Gabriele Mongiano; Alessandra Lagomarsino; Simone Bregaglio (Journal of Cleaner Production, 2024)

Balanced NPK Nutrition Improves Forage Productivity and Quality of Pearl Millet Grown in Semi-arid Regions of Pakistan - Ahmad Sher; Zahid Ali Akbar; Abdul Sattar; Sami Ul-Allah; Muhammad Ijaz; Roberta Calone; Lorenzo Barbanti (Journal of Soil Science and Plant Nutrition, 2023)

Neem and Castor Oil–Coated Urea Mitigates Salinity Effects in Wheat by Improving Physiological Responses and Plant Homeostasis - Imran Khan; Sadia Muhammad Ali; Muhammad Umer Chattha; Lorenzo Barbanti; Roberta Calone; Athar Mahmood; Tasahil S. Albishi; Muhammad Umair Hassan; Sameer H. Qari (Journal of Soil Science and Plant Nutrition, 2023)
Soil salinity is abiotic stress of growing concern, whose effects can be potentially mitigated by the use of suitable fertilisers. Based on this, an experiment was conducted to determine the role of vegetable oil–coated urea on the performance of wheat ( Triticum aestivum ) under salinity. Neem oil–coated urea (NOCU), castor oil–coated urea (COCU), and normal urea (NU) were compared in wheat plants growing in pots at three soil salinity levels (0, 6, and 12 dS m -1 ). Plant morphology, growth, element contents (Na, Cl, K, and N), and several traits were assessed at the flag leaf stage; biological yield, grain yield, and its components were assessed at maturity. Salinity stunted growth (approximately -50% yield with high salinity vs. control); boosted Na and Cl concentrations while abating K and N concentrations in plant organs; impaired leaf water status; reduced photosynthetic pigments and increased antioxidant activities and osmo-regulating compounds. NOCU and, to a lesser degree, COCU mitigated salinity effects by upgrading antioxidant activities, reducing oxidative stress markers, increasing leaf water status, photosynthetic pigments, and osmo-regulating compounds. However, NOCU under high salinity could only achieve the levels of NU under intermediate salinity. Lastly, NOCU and COCU restricted plant entry of adverse ions (Na and Cl) while increasing K and N accumulation. Vegetable oil–coated urea, namely NOCU, significantly contributed to improving wheat behaviour and final yield under salinity. These outcomes are associated with the two fertilisers’ properties of slow nitrogen release.